Implementasi Green Human Resource Management: Analisis Strategi Dalam Mengintegrasikan Prinsip Lingkungan Kerja Terhadap Employes Performance Dimoderasi Kebijakan : Implementasi Green Human Resource Management: Analisis Strategi Dalam Mengintegrasikan Prinsip Lingkungan Kerja Terhadap Employes Performance Dimoderasi Kebijakan - Rosalinda, Ursula Uci (Lembaga Kajian Pertahanan Strategis, 2024)
The aim of this research is to determine the significant influence of Green Recruitment, Green Training and Development, Green Performance Management on Employee Performance through the GHRM Policy as a Moderation variable. The research methodology uses a saturated sample where the population used as research subjects are employees of PT. Alexindo with 120 respondents. Smart PLS 3.2 statistical test with results; 1) Gren Recruitment has a positive and significant effect on Employee Performance with a p-Value of 0.045. 2) Gren Recruitment has a positive and significant effect on GHRM Policy with a p-Value of 0.000. 3) Green Training and Development has a positive and significant effect on Employee Performance with a p-Value of 0.002. 4) Green Training and Development has a positive and significant effect on GHRM Policy with a p-Value of 0.000. 5) Green Performance Management has a positive effect on Employee Performance with a p-Value of 0.014. 6) Green Performance Management has a positive and significant effect on GHRM Policy with a p-Value of 0.000. 7) GHRM policy has a positive but not significant effect on Employee Performance with a p-Value of 0.155. The indirect hypothesis 8) Green Recruitment on Employee Performance through the mediation of the GHRM Policy gets a P-Value of 0.115 and the Original Sample is 0.048, which means this variable has a positive but not significant effect. 9) Green Training and Development on Employee Performance through the mediation of the GHRM Policy obtained a P-Value of 0.182 and Original Sample 0.031, which means this variable has a positive but not significant effect. 10) Green Performance Management on Employee Performance through the mediation of the GHRM Policy obtained a P-Value of 0.171 and Original Sample 0.026, which means this variable has a positive but not significant effect. Keywords: Green Recruitment, Green Training and Development, Green Performance Management, Employee Performance, GHRM